A&T Bangladesh Urban Maternal Nutrition Endline Survey 2022: Antenatal Care Case Observation - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
This dataset is the result of the Case Observation survey that was conducted to gather data for the endline part of the impact evaluation study of the Alive & Thrive (A&T) interventions delivered through the Urban Maternal, Neonatal and Child Health (MNCH) Services in Bangladesh. These include building capacity for health providers and nutritional counselors in urban health clinics, creating friendly environment for maternal infant, and young child nutrition (MIYCN) counseling in clinic settings, community mobilization for demand creation of MIYCN services, interpersonal counseling on diet during pregnancy and consumption of iron-folic acid (IFA) and calcium, promotion of adequate weight-gain monitoring during pregnancy, and counseling on breastfeeding and complementary feeding practices. A&T is a global initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding, and complementary feeding practices. Using a quasi-experimental design, the primary objectives of the A&T evaluation study in Bangladesh are to answer the following questions: -What are the impacts of standardized and upgraded MIYCN counselling services on behaviors of clients including: -Pregnant women: 1) consumption of diversified foods; 2) intake of IFA and calcium supplements during pregnancy -Mothers of children <12 months: age-appropriate infant feeding -Is it feasible to standardize the delivery of MIYCN counselling services in existing urban health facilities? -Can the quality of MIYCN counselling services be improved by upgrading and standardizing existing MIYCN counselling services in urban health facilities? -What are the impacts of standardized and upgraded MIYCN counselling service on the utilization of MIYCN services?